2018
DOI: 10.1136/heartjnl-2018-313585
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac consequences of spinal cord injury: systematic review and meta-analysis

Abstract: ObjectiveConduct a meta-analysis to determine the impact of traumatic spinal cord injury (SCI) on echocardiographic measurements of left ventricular (LV) structure and function.MethodsMEDLINE and Embase were used for primary searches of studies reporting LV echocardiographic data in individuals with SCI. Of 378 unique citations, 36 relevant full-text articles were retrieved, and data from 27 studies were extracted for meta-analyses. Literature searches, article screening and data extraction were completed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 37 publications
3
49
2
Order By: Relevance
“…In the present study, we observed similar percentage decreases with only a 45° head‐up tilt in individuals with cervical SCI, for whom LVEDV and LVSV are already reduced compared to able‐bodied individuals (Williams et al . ). Reduced LV volumes in response to tilt further highlight the challenges faced by athletes with cervical SCI with respect to mounting a normal cardiovascular response to exercise in the seated position.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, we observed similar percentage decreases with only a 45° head‐up tilt in individuals with cervical SCI, for whom LVEDV and LVSV are already reduced compared to able‐bodied individuals (Williams et al . ). Reduced LV volumes in response to tilt further highlight the challenges faced by athletes with cervical SCI with respect to mounting a normal cardiovascular response to exercise in the seated position.…”
Section: Discussionmentioning
confidence: 97%
“…Our present data extend these observations from the chronic setting by demonstrating that LV contractility is impaired immediately following high-level SCI. Importantly, we highlight that EF was unchanged despite clear reductions to LV contractility, reinforcing that EF does not adequately detect systolic or contractile dysfunction in SCI 11 . We have additionally identified a reduction to LV contractile reserve acutely after the injury, which may be attributable to a rapid loss of ‘baseline’ contractility and tonic neuro-hormonal activation of the myocardium that occurs following high-level SCI.…”
Section: Discussionmentioning
confidence: 77%
“…In experiment 1, the immediate reductions to key load-independent measures of LV systolic function incontrovertibly indicates that intrinsic contractile dysfunction in high-level SCI results from the immediate loss of descending sympathetic input following high-level injury. Previously, only a small collection of echocardiographic studies in humans had provided some evidence for chronically-altered LV systolic function in humans 11 , and the interpretation of those findings were limited due to the load-dependent nature of echo-derived data. To assess load-independent LV function our group has utilized LV pressure-volume catheterization in a chronic rodent model of SCI and reported reductions to LV E es after a T2 injury 12,13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic haemodynamic ‘unloading’ of the heart following SCI causes substantial cardiac atrophy (Williams et al . ). As such, interventions that mitigate the harmful effects of this degeneration are crucial to help maintain exercise performance and offset cardiorespiratory dysfunction.…”
Section: Heart–lung Interactionmentioning
confidence: 97%